Balanced Nutrition and Nutrition Status of Schoolchildren in Rural Areas of Ogan Komering Ilir District South Sumatra Indonesia - Fatmalina Febry; Anita Rahmiwati; Ditia Fitri Arinda (Faculty of Public Health, Sriwijaya University, 2021)
To support the growth and development of children and adolescents, a balanced nutritious diet is required. Indonesia issues a balanced nutrition guideline as the government's effort to overcome various nutritional problems in Indonesia.  This study aimed to evaluate the relationship among four pillars of balanced nutrition, namely eating a variety of foods, monitoring body weight, hygiene and healthy living habits and physical activity with nutritional status in school children. This study used a cross-sectional method which was conducted in elementary schools in rural areas with a number of sample of 80 schoolchildren with  purposive sampling technique. The data were taken directly by means of interviews and anthropometric measurements. Based on the results of the study, there was a relationship between various foods and physical activity with nutritional status, while for the clean and healthy living habits and monitoring of body weight there was no relationship to the nutritional status of school children.  There was a relationship between diverse foods and physical activity and nutritional status of schoolchildren in rural areas of Ogan Komering Ilir District.